Developmental differences in the prospective organisation of goal‐directed movement between children with autism and typically developing children: A smart tablet serious game study. Issue 3 (6th December 2021) - Chua, Yu Wei; Lu, Szu‐Ching; Anzulewicz, Anna; Sobota, Krzystof; Tachtatzis, Christos; Andonovic, Ivan; Rowe, Philip; Delafield‐Butt, Jonathan
Abstract: Movement is prospective. It structures self‐generated engagement with objects and social partners and is fundamental to children's learning and development. In autistic children, previous reports of differences in movement kinematics compared to neurotypical peers suggest that its prospective organisation might be disrupted. Here, we employed a smart tablet serious game paradigm to assess differences in the feedforward and feedback mechanisms of prospective action organisation, between autistic and neurotypical preschool children. We analysed 3926 goal‐directed finger movements made during smart‐tablet ecological gameplay, from 28 children with Childhood Autism (ICD‐10; ASD) and 43 neurotypical children (TD), aged 3–6 years old. Using linear and generalised linear mixed‐effect models, we found the ASD group executed movements with longer movement time (MT) and time to peak velocity (TTPV), lower peak velocity (PV), with PV less likely to occur in the first movement unit (MU) and with a greater number of movement units after peak velocity (MU‐APV). Interestingly, compared to the TD group, the ASD group showed smaller increases in PV, TTPV and MT with an increase in age (ASD × age interaction), together with a smaller reduction in MU‐APV and an increase in MU‐APV at shorter target distances (ASD × Dist interaction). Our results are the first to highlight different developmental trends in anticipatory feedforward and compensatory feedback mechanisms of control, contributing to differences in movement kinematics observed between autistic and neurotypical children. These findings point to differences in integration of prospective perceptuomotor information, with implications for embodied cognition and learning from self‐generated action in autism.